The Contestability Paradigm in the Presence of Vertical Differentiation: Entering the Incumbent's Quality Niche - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1992)
The aim of this paper is to analyse the interaction between vertical differentiation and contestability in the context of a repeated game with discounting. It is shown that, if consumers retaliate after hit-and-round entry and suppliers and reasonably low discount rates, contestability may not hold.
Keywords: 330